Novel biosensor for highly sensitive detection of serum albumin in artificial human urine using CuNPs@AG - Awaz Sayfallah Sami; Sabah Subhi Ismael Barani; Rzgar Farooq Rashid; Samie Yaseen Sharaf Zeebaree; Aymn Yaseen Sharaf Zeebaree; Osama Ismail Haji Zebari; Ali Mousa Ali; Khalaf Simo Ilyas; Falah Hasan Biso; Muhammad Mirhaj Issa (Sensing and Bio-Sensing Research, 2024)
Detecting early signs of disease can significantly mitigate the risk of severe consequences. Chronic kidney disease (CKD), stemming from various underlying conditions like diabetes mellitus, high blood pressure, obesity, and heart disease, manifests as an impairment in the kidneys' ability to efficiently filter blood. Consequently, a small amount of the protein albumin might be excreted into the urine. In this study, we have developed a novel biosensor utilizing copper nanoparticles to identify even trace levels of albumin in urine samples. Unlike conventional immunoassay methods, our biosensor doesn't rely on antibodies for its creation. By utilizing gum tree as a stabilizing agent, we've successfully synthesized the copper nanosensor, achieving distinct optical properties and prolonged stability. This method allowed for the precise quantification of bovine serum albumin (BSA) under optimized conditions. To perform quantitative analysis, we established a calibration curve by plotting the variations in absorbance at 580 nm between the sample and the blank. This assay effectively detected albumin within the concentration range of 25 to 250 mg/L (with an R2 value of 0.98), and it exhibited a low limit of detection (LOD) at 6.5 mg/L. Notably, CuNPs demonstrated excellent specificity towards albumin. Moreover, we successfully applied this developed method for the rapid screening of albumin in synthetic and authentic urine samples, achieving recovery percentages ranging from 90% to 104% using UV–visible spectrometry. Overall, this colorimetric method holds significant promise for on-site albumin detection, offering high accuracy, exceptional selectivity, and minimal reagent consumption.